SCL/Tal-1 transcription factor acts downstream of cloche to specify hematopoietic and vascular progenitors in zebrafish - Liao, Eric C. (Cold Spring Harbor Laboratory Press, 1998)
SCL/Tal-1 is a transcription factor necessary for hematopoietic stem cell differentiation. Although SCL is also expressed in endothelial and neural progenitors, SCL function in these cells remains unknown. In the zebrafish mutant cloche (clo), SCL expression is nearly abolished in hematopoietic and vascular tissues. Correspondingly, it was shown previously that clo fails to differentiate blood and angioblasts. Genetic analysis demonstrates that the clo mutation is not linked to the SCL locus. Forced expression of SCL in clo embryos rescues the blood and vascular defects, suggesting that SCL acts downstream of clo to specify hematopoietic and vascular differentiation.